Sensitivity of chest ultrasound for postoperative pneumothorax in comparison to chest X-ray after lung resecting surgery. (4th December 2019) - Galetin, Thomas; Defosse, Jérôme; Schieren, Mark; Marks, Ben; Lopez-Pastorini, Alberto; Koryllos, Aris; Kosse, Nils; Wappler, Frank; Stoelben, Erich
Abstract: OBJECTIVES: Thoracic ultrasound is superior to chest X-ray for the detection of a pneumothorax in trauma and intensive care medicine. Data regarding its use in non-cardiac thoracic surgery are scarce and contradictory. Previous studies are heterogeneous regarding sonographic methodology and patient selection. This study aimed to evaluate the accuracy of thoracic ultrasound for pneumothorax assessment after lung resecting surgery in unselected patients. METHODS: SONOR ( SONO graphy vs x- R ay) is a prospective observational trial (registry-ID DRKS00014557). A total of 123 consecutive patients with lung resecting surgery received a standardized thoracic ultrasound the same day and in addition to routine chest X-rays in erect position after removal of the chest tube. The sonographer was blinded to radiological findings and vice versa. RESULTS: Sensitivity, specificity, positive and negative predictive values of ultrasound after removing the chest tube were 0.32, 0.85, 0.54, 0.69 for any pneumothorax and 1.0, 0.82, 0.19, 1.0 for pneumothorax ≥3 cm. No clinically relevant pneumothorax was missed. The agreement between sonography- and routine-based therapeutic decisions was 97%. Lung pulse was the most frequently detected sign to sonographically rule out a pneumothorax. CONCLUSIONS: Postoperative thoracic ultrasound in unselected patients has a low overall sensitivity to detect a residual pneumothorax; however, its sensitivity and negative predictive values regarding clinically relevant pneumothorax are high. Test quality depends on the distinct sonographic methodology and patient selection. Anatomic differences in postsurgical and medical patients may be responsible for the contradictory results of previous trials. Studies with a larger population size are required to validate the accuracy of relevant pneumothoraces and identify appropriate selection criteria. Clinical trial registration number: DRKS—German Clinical Trials Register, www.drks.de, registry-ID DRKS00014557 .